2020
DOI: 10.1038/s41598-020-79270-6
|View full text |Cite
|
Sign up to set email alerts
|

The RabGEF ALS2 is a hypoxia inducible target associated with the acquisition of aggressive traits in tumor cells

Abstract: Tumor hypoxia and the hypoxia inducible factor-1, HIF-1, play critical roles in cancer progression and metastasis. We previously showed that hypoxia activates the endosomal GTPase Rab5, leading to tumor cell migration and invasion, and that these events do not involve changes in Rab protein expression, suggesting the participation of intermediate activators. Here, we identified ALS2, a guanine nucleotide exchange factor that is upregulated in cancer, as responsible for increased Rab5-GTP loading, cell migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
(69 reference statements)
1
12
0
Order By: Relevance
“…The observation that Rab5 gets activated in recipient endothelial cells treated with hypoxic sEVs and the dependency of Rab5 activity on sEVs-induced endothelial cell migration, prompted us to investigate the mechanisms underlying such activation. In this respect, previous studies by our group identified the Rab guanine exchange factor (GEF) ALS2 as responsible for Rab5 activation in hypoxic tumor cells (23). Remarkably, we found that tumor cell-derived sEVs contained ALS2 as cargo, and that this was further increased in hypoxia (Figure 5A, B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The observation that Rab5 gets activated in recipient endothelial cells treated with hypoxic sEVs and the dependency of Rab5 activity on sEVs-induced endothelial cell migration, prompted us to investigate the mechanisms underlying such activation. In this respect, previous studies by our group identified the Rab guanine exchange factor (GEF) ALS2 as responsible for Rab5 activation in hypoxic tumor cells (23). Remarkably, we found that tumor cell-derived sEVs contained ALS2 as cargo, and that this was further increased in hypoxia (Figure 5A, B).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we observed that hypoxic sEVs increase both the amount and size of Rab5-positive structures in recipient EA.hy926 cells (Figure 4D-F), which was in agreement with data obtained for EEA1-positive structures (Figure 4A). Since Rab5 activity is required for endothelial cell responses and based on previous evidence indicating that Rab5 gets activated under hypoxic conditions (23, 24), we hypothesized that sEVs released by hypoxic tumor cells activate Rab5 in recipient endothelial cells, resulting in increased angiogenic-related responses. We first determined the effects normoxic and hypoxic sEVs on EAhy.926 cells, observing that hypoxic sEVs promote Rab5-GTP loading in recipient endothelial cells, as compared with those cells treated with normoxic sEVs (Figure 4G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these 111 PSGs in V. ferrilata, 20 PSGs related to high-altitude environmental selection stress mainly include the following five aspects: DNA damage repair (LIG4, ZNF830, CRTAC1, and GRB2) (Jun et al, 2016;Chen G. et al, 2018;Hou et al, 2019;Félix et al, 2021), energy metabolism (ARF6 and IRS1) (Dong et al, 2006;Gamara et al, 2021), myocardial growth (EIF3A, IL6ST, SIRT4, and MZB1) (Luo et al, 2016;Klimushina et al, 2019;Miao et al, 2019;Zhang et al, 2021), angiogenesis (IGFBP3, RND3, APLNR, RBPJ, and ARHGEF15) (Lofqvist et al, 2007;Kusuhara et al, 2012;Díaz-Trelles et al, 2016;Mastrella et al, 2019;Wu et al, 2021), and hypoxia stress response (RHEB, WWOX, COMMD1, LAMA4, and PNN) (He et al, 2017;Murata et al, 2017;Hsu et al, 2020;Baryla et al, 2022;Cai et al, 2022). In contrast, PSGs related to altitude adaptation in V. v. montana only has DNA damage repair (C19ORF57) (Takemoto et al, 2020) and hypoxia response related to HIF1-α regulation (FUT11, USP8, CASP14, VGLL4, and ALS2) (Troilo et al, 2014;Ye et al, 2018;Rivas et al, 2020;Wang et al, 2020;Ruan et al, 2021). In addition to the species-specific PSGs related to altitude adaptation, two of the four PSGs (TCF20 and KRAS) shared by V. ferrilata and V. v. montana are also related to altitude adaptation.…”
Section: Discussionmentioning
confidence: 99%